If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -2 * -4 = w Multiply -2 * -4 3 + 8 = w Combine like terms: 3 + 8 = 11 11 = w Solving 11 = w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-1w' to each side of the equation. 11 + -1w = w + -1w Combine like terms: w + -1w = 0 11 + -1w = 0 Add '-11' to each side of the equation. 11 + -11 + -1w = 0 + -11 Combine like terms: 11 + -11 = 0 0 + -1w = 0 + -11 -1w = 0 + -11 Combine like terms: 0 + -11 = -11 -1w = -11 Divide each side by '-1'. w = 11 Simplifying w = 11
| 4(x+6)=6(x-2)+3x-4 | | y=2x^2-12x-19 | | (2x-1)+2(2x+6)=4x-1 | | (2p+3)(2p-3)=(2p+10)(2p-10)-91p | | 3h+13h=20-2 | | 6x+7=3x+8 | | 2x+3(x-2)=4x-24+2x | | 6*-2=r-5r | | 7(x-9)-5=-68 | | 6*-2=r | | 15x=482 | | 3y-1+y+35=7+7y+33-5y | | 8w+6w=82 | | (x-4)2=(x-2) | | 4-t=2xa+21 | | 15x=498 | | x^2+27x-468=0 | | y^2-16y^2=0 | | 6x-5+8y=-22 | | -5*-3=15-7c | | x-9x=-4*6 | | (8+w)(2w+9)=0 | | 6-2n=1-8n+5 | | 3x+5-6x=10+2x | | -2(z+3)-z=-z-5(z+2) | | x^6+3x^3-4= | | 17x=8x+8 | | -2*-4=o | | 4x-2+2x-5=77 | | 4(5z-1)-5(2+9)=2(z+1) | | 2*-4=o | | -2*-4=ourfgn |